"Blister Beetles (Coleoptera: Meloidae) in Nahavand County (Hamedan Province, Iran) and Their Ecological Relationship to Other Coleopteran Families" - MR Nikbakhtzadeh; S Tirgari (Tehran University of Medical Sciences, 2002)
Field collection in Nahavand county (Hamedan Province, Iran) revealed 9 blister beetle (Col: Meloidae) species from three different tribes of subfamily Meloinae. In tribe Mylabrini, Mylabris impressa Chevrolat 1837, Mylabris schreibersi Reiche 1865, Mylabris variabilis (Pallas, 1781), Mylabris guerini Chevrolat 1837, Lydoceras bilineatus Thomas 1897 and Croscherichia spp. Pardo Alcaide identified; whereas in tribe Lyttini Alosimus smyrnensis (Maran 1942) and Muzimes iranicus (Maran 1942) found. Another species was Calydos alloushei Kaszab 1960 of tribe Eupomphini. Two records of Mylabris impressa and Mylabris schreibersi are quite new for Iranian fauna. There are some interesting mimicry rings between meloid species and 8 species of other coleopteran families which indicates a remarkable Müllerian mimicry. Mimics of the following families have taken advantage of Meloid aposematism towards a better natural fitness: Cerambycidae, Cleridae, Pedilidae, Melyridae, Chrysomelidae, Cantharidae and Cicindelidae. Canthariphily of families Chrysomelidae, Cantharidae and Cerambycidae are new reports which have never been shown elsewhere.